CRITICAL THINKING DEVELOPMENT IN FOREIGN LANGUAGE LEARNING AT HIGHER EDUCATION INSTITUTIONS: PHILOSOPHICAL AND ANTHROPOLOGICAL DIMENSIONS - Kuzmenko, Raisa; Krylova, Svitlana; Shkil, Liudmyla (Proceedings of the National Aviation University Series Philosophy Cultural, 2024)
The study is based on the achievements of ancient thinkers on the process of thinking, modern foreign and domestic authors in the approach to the interpretation of critical thinking and methods of its improvement by means of language learning. The hermeneutic and comparative approaches were used to achieve the goal and solve the tasks set in the work. These methods allowed authors to analyze the concepts of "critical thinking" and "distance learning". The modern vision of the concept of "critical thinking" is seen as the ability of an individual to analyze, argue statements or evidence, and draw conclusions using various models of reasoning, which ensures the processes of self-knowledge, self-education, and self-realization. The ability to think critically is a must for today. It is proved that critical thinking is a prerequisite for the development of the individual and society, while education is its guarantor. The modern distance approach is the main one in the paradigm of foreign language learning and critical thinking development.